2010
DOI: 10.1021/nn901586e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Cytoplasmic Delivery of Proteins To Target Cellular Machinery

Abstract: Despite recent advances in nanomaterial-based delivery systems, their applicability as carriers of cargo, especially proteins for targeting cellular components and manipulating cell function, is not well-understood. Herein, we demonstrate the ability of hydrophobic silica nanoparticles to deliver proteins, including enzymes and antibodies, to a diverse set of mammalian cells, including human cancer cells and rat stem cells, while preserving the activity of the biomolecule post-delivery. Specifically, we have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 32 publications
2
116
0
Order By: Relevance
“…Most of those efforts were successful in delivering small molecule drugs (S. R. Yang et al, 2006), proteins (Bale et al, 2010) and nucleic acids to specific organelle inside cell. The major advantage of use of nanocarriers in cytosolic delivery arises from their characteristic properties like nanosize (1-100 nm), ability to carry high drug/gene payload, feasibility to modify the surface functionality for active targeting, ability to utilize its surface charge for passive targeting.…”
Section: Role Of Nanocarriers In Cytosolic Deliverymentioning
confidence: 99%
“…Most of those efforts were successful in delivering small molecule drugs (S. R. Yang et al, 2006), proteins (Bale et al, 2010) and nucleic acids to specific organelle inside cell. The major advantage of use of nanocarriers in cytosolic delivery arises from their characteristic properties like nanosize (1-100 nm), ability to carry high drug/gene payload, feasibility to modify the surface functionality for active targeting, ability to utilize its surface charge for passive targeting.…”
Section: Role Of Nanocarriers In Cytosolic Deliverymentioning
confidence: 99%
“…Recently, Surface enhanced Raman spectroscopy (SERS) has been used for a large variety of bioanalytical applications, including single molecule studies, 1 oligonucleotide sequencing 2 and for probing peptide and protein structure. [3][4][5][6] SERS can also be used for imaging the intracellular environment of cells and has been demonstrated using a variety of noble metal particles which are readily delivered to mammalian cells. 4,7,8 Gold nanoshells (NS) are engineered nanoparticles and we have recently demonstrated that their characteristics make them ideal for intracellular SERS studies.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] SERS can also be used for imaging the intracellular environment of cells and has been demonstrated using a variety of noble metal particles which are readily delivered to mammalian cells. 4,7,8 Gold nanoshells (NS) are engineered nanoparticles and we have recently demonstrated that their characteristics make them ideal for intracellular SERS studies. 5,[9][10][11][12][13] We have also recently demonstrated that NS are ideal substrates for the measurement of conformational changes in biomolecules and that this property can be used for direct measurement of biomolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bale and co-workers reported the octadecyl funtionalized stober spheres for efficient intracellular delivery of a hydrophobic cytotoxic proteinRNase A. 59 Very recently, our group also reported the octadecyl funtionalized silica hollow spheres allowed very high RNase A loading amount (~850 mg/g) and sustained release for more than 3 days. 51 Such a nanoparticle-protein composite induced significantly enhanced cell inhibition compare to bare protein due to its cell membrane impermeability.…”
Section: Composition and Surface Functionlizationmentioning
confidence: 78%
“…In contrast, the cell inhibition in the presence of MOSNs-7.6-RNase A exhibits a time dependent manner at the same protein dosage, where the cell death increases from 40% at 24 h to 56% at 48 h and finally 64% at 72 h. The significantly enhanced cytotoxicity of MOSNs-7.6-RNase A compared to pure RNase A should be attributed to the sufficient loading capacity, sustained release and efficient cell uptake of MOSNs-7.6 as demonstrated above. Compared to previous silica based RNase A delivery systems using octadecyl modified solid silica nanoparticles (effective dosage 35 μg/ml) [59] and octadecyl modified hollow silica NPs (effective dosage 8 μg/ml) [115] , MOSNs-7.6 exhibits a much lower effective RNase A dosage (4 μg/ml) to cancer cells without the need of any post functionalization, which is believed very advantageous for a convenient protein deliver system with lowered side effects. However, as expected, MOSNs-4.6-RNase A shows very limited cell inhibition ability of ~32% at three time points (Figure S9), which is mainly attributed to the rapid protein release profile.…”
Section: Iron Oxidementioning
confidence: 94%